(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: To compare the outcome medial parapatellar (MPA) and transpatellar (TPA) approaches for static interlocked nail in tibial shaft fractures in terms of post-operative pain and range of motion. Material and Methods: Study design randomized controlled trial in the department of orthopedic surgery, Jinnah Hospital Lahore in duration of 6 months. A sample size of 56 (28 in each group) was calculated by assuming the mean postoperative pain with medial parapatellar approach 3.06±1.83 compared to the transpatellar 4.53±2.04, at confidence interval of 95% and power 80%. This was calculated by using OpenEpi online software calculator. (8) Sampling technique was non-probability consecutive sampling technique. Inclusion criteria as patients aged 18-60 years regardless of gender, individuals diagnosed with acute tibial shaft fractures, confirmed by radiographic imaging, patients having Gustilo and Anderson type I, II, IIIA, and patients who were willing and able to provide informed consent for participation in the study.Statistical analysis included as data was analyzed using SPSS version 26.0. Categorical variables (type of fracture, gender) were reported as frequency and percentages. Continues variables (VAS pain score, range of motion for flexion and extension, age, duration of fracture, BMI) was reported as mean and standard deviation. Outcomes (Range of motion, VAS pain score) between two groups were compared using independent t-test. Data was stratified for age, gender, duration of fracture and type of fracture, post-stratification unpaired t-test was applied to see the effect of these potential effect modifiers on the outcome. A p-value of <0.05 was considered statistically significant. Results:In this randomized controlled trial of 56 patients with tibial shaft fractures, the medial parapatellar approach (MPA) demonstrated statistically significant superiority over the transpatellar approach (TPA) in reducing post-operative pain and improving knee range of motion. At both 2 weeks and 3 months, MPA patients reported lower VAS pain scores (p = 0.001 and p = 0.002, respectively) and achieved greater knee flexion (p = 0.001 and p = 0.003, respectively). These benefits were consistent across age, gender, fracture type, and BMI subgroups, confirming MPA as a more effective and reliable technique for static interlocked nailing in tibial fractures. Conclusion:This randomized controlled trial provides robust evidence that the medial parapatellar approach (MPA) is superior to the transpatellar approach (TPA) for static interlocked intramedullary nailing in the management of tibial shaft fractures (Gustilo-Anderson types I, II, and IIIA). Patients in the MPA group demonstrated significantly lower post-operative pain scores at both 2 weeks (p = 0.001) and 3 months (p = 0.002), alongside significantly greater knee flexion range of motion at the same intervals (p = 0.001 and p = 0.003, respectively). These advantages were consistent across all stratified subgroups including age, gender, BMI, and fracture type indicating that the benefits of MPA are not confined to specific patient profiles but are broadly generalizable.